2012
DOI: 10.1128/aem.07893-11
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Yersinia enterocolitica in Pigs Slaughtered in Chinese Abattoirs

Abstract: ABSTRACTThe distribution ofYersinia enterocoliticain slaughtered pigs in China was studied. A total of 8,773 samples were collected and examined from different pig abattoirs in 11 provinces from 2009 to 2011. Of these, 4,495 were oral-pharyngeal swab (tonsils) samples from pigs, 1,239 were from intestinal contents, and 3,039 were feces samples from abattoirs or local pigpens. The data showed that 1,132 strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 30 publications
4
39
0
Order By: Relevance
“…Macrorestriction analysis was performed to investigate the clonality of the isolates. NotI (Roche Diagnostics, Mannheim, Germany)-digested fragments of genomic DNA were separated in a CHEF DR II system (Bio-Rad, Munich, Germany) as described by Liang and coworkers (30). The total run time was 19 h, and 0.5ϫ Tris-borate-EDTA buffer was used as the running buffer.…”
Section: Species Identification By Maldi-tof Ms and Cultivation Of Ismentioning
confidence: 99%
“…Macrorestriction analysis was performed to investigate the clonality of the isolates. NotI (Roche Diagnostics, Mannheim, Germany)-digested fragments of genomic DNA were separated in a CHEF DR II system (Bio-Rad, Munich, Germany) as described by Liang and coworkers (30). The total run time was 19 h, and 0.5ϫ Tris-borate-EDTA buffer was used as the running buffer.…”
Section: Species Identification By Maldi-tof Ms and Cultivation Of Ismentioning
confidence: 99%
“…Y. pseudotuberculosis and Y. enterocolitica are zoonotic food-borne pathogens that spread through the fecal-oral route; they have a broad host range, infecting animals, including swine, dogs, rodents, birds, and wild animals (3,4). Many studies show that swine and dogs are the most common sources of Y. enterocolitica infections in humans (5,6). These enteropathogens cause human enteric diseases, both sporadically and in epidemics worldwide.…”
mentioning
confidence: 99%
“…Additionally, the important virulence genes are usually missing in animal strains. Human pathogenic strains of Y. enterocolitica typically have been isolated from slaughtered fattening pigs (Fredriksson-Ahomaa et al 2007b;Ortiz Martínez et al 2010;Vanantwerpen et al 2013;Liang et al 2012). Recently, it was shown that there can be a large variation in the within-batch prevalence among pig farms (Vanantwerpen et al 2013).…”
Section: Prevalence In Animalsmentioning
confidence: 99%